Analysis of Early Marriage Satisfaction in Muslim Families - Rasdiany, Apriana Nofriastuti; Latifa, Aulia; Mutathahirin, Mutathahirin; Oktavia, Gifa; Febriani, Afifah; Kakoh, Nur Asikin (El-Rusyd, 2024)
Early marriage is a significant sociocultural phenomenon, especially among Muslims, which is influenced by various religious, economic, and social factors. This study aims to analyze the marital satisfaction of couples who married at a young age. This research was conducted using quantitative methods with a survey approach. The data source was taken using a questionnaire from 32 married couples who married at a young age with the category that the husband was under 25 years old at the time of marriage, while the wife was under 21 years old. All data was then analyzed using SPPS Windows Version 20 software. Overall, the statistical analysis results showed that 32 married couples stated that they were satisfied with their partners while building a household. Marital satisfaction in question is measured through six aspects, namely; aspects of communication, conflict resolution, finances, sexual relations, the role of each husband and wife in the family, and religious life. This means that the six aspects used as instrument items in this research were felt to be satisfactory by all married couple after getting married. The results of this study have at least refuted the assumption that marrying at a young age tends to fail. In other words, age at marriage does not determine success in the household. The success of a marriage is determined if the husband and wife know their respective roles and responsibilities well.